Extremely Preterm (23 Weeks) Vaginal Cephalic Delivery En Caul and Subsequent Postpartum Intraventricular Hemorrhage and Respiratory Distress: A Teaching Case - Rohail Malik; Adil Sarfraz; Raihan Faroqui; William Onyebeke; Jeffrey Wanerman (Case Reports in Obstetrics and Gynecology)
En caul deliveries are defined as a fetus that is delivered completely contained within an amniotic sac and are considered to be less common than 1 in 80,000 live births. Vaginal en caul births compared to abdominal or cesarean are the rarest subtype. Most en caul births are associated with prematurity and low gravida. The combination of prematurity, high gravida, vaginal en caul birth, and severe postpartum complications has not previously been described. We report a woman with gravida of 12 delivering vaginally a neonate female en caul at the extremely preterm gestational age of 23 weeks. The neonate subsequently decompensated, underwent respiratory distress, and was diagnosed with a bilateral intraventricular hemorrhage. Owing to deteriorating status, supportive care was removed and the infant was pronounced dead 5 days after delivery.